Implementation of Max-Plus Algebra on Image Steganography with Bicover - Fiisyatil Kamilah; Nur Hamid (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2026)
This study proposes a steganography method based on the bicover concept by utilizing Max-Plus algebra through matrix multiplication operations without inverse. The proposed method uses two cover images to embed one secret image, namely the first cover image to store the MSB (Most Significant Bit) bit and the second cover image to store the LSB (Least Significant Bit) bit. The test results show that this method is able to reconstruct the secret image completely with good stego image quality. The PSNR value obtained is 31.18 dB in Stego 1 and 31.77 dB in Stego 2, while the MSE value is 49.5457 in Stego 1 and 43.2352 in Stego 2. These results indicate that the visual changes in the container image are relatively small so that the existence of the secret image is difficult to recognize. Thus, the proposed method can be an alternative in improving the security of digital data exchange.